IMPLEMENTASI PROSEDUR PEMUNGUTAN DAN PENYETORAN PPh PASAL 22 DI LINGKUNGAN SEKRETARIAT KABINET RI - Annisa Mardiani Safira, (2023)
This Final Project Report discusses the implementation of procedures for collecting and depositing Income Tax Article 22 in the Cabinet Secretariat of the Republic of Indonesia from October to December 2022. Tax is a state contribution that obliges taxpayers to pay taxes forcibly without any return. Income Tax 22 is a form of tax collection or withholding imposed by taxpayers who trade in goods. The purpose of this analysis is to know and study how to collect and deposit Income Tax Article 22 at the Cabinet Secretariat of the Republic of Indonesia. This analysis is carried out knowing the flow of collection and deposit of Income Tax Article 22. The treasurer calculates and collects to determine the amount of Income Tax Article 22 and then deposits it in 2 ways, namely Transfer and Cash. Transfers are made using Mbanking BNI and Cash must make a Billing Code at DJPOnline then paid to Bank BNI after that the billing code and proof of deposit are inputted into SAKTI and get a Tax Payment Slip. The billing code and document files are inputted into SPANINT.